Predicting factor of remission in persons with schizophrenia,Srithaya Hospital - Benjehma , Rattiyaporn; Upasen , Ratchaneekorn (Nursing Journal CMU, 2020)
Schizophrenia is one of the major issue on psychiatric problems. The effect of schizophrenia is usually severe and chronic, however the current treatment has been advanced so that many symptoms can be managed easier. The purpose of this descriptive research was to determine predictors of remission in persons with schizophrenia. The factors predicting variables were gender, duration of untreated psychosis, duration of illness, cognitive insight, medication adherence, highly-expressed emotion in family, and cognitive function. Subjects were persons with schizophrenia treated as in-patients and out-patients in Srithanya Hospital chosen purposively. A total of 220 patients were equally divided into two groups: remission and non-remission. The research instruments were demographic interview, The Beck Cognitive Insight Scale, medication adherence behavior questionnaire, The Level of Expressed Emotion, and Thai Mini-Mental State Examination. Data were analyzed by logistic regression. The result was that factors predicting of remission in schizophrenic patients include three variables could significantly at the .05 levels were namely, cognitive function, medication adherence and cognitive insight. The logistic response formula were: Predited logit (remission in persons with schizophrenia) = -13.066 + 0.130*(insight) +0.071*(medication Adherences) + 0.325*(cognitive function). These predictors were accounted for 46.8 percent. Thus, medication adherence and cognitive function are factors that persons with schizophrenia should have and be promoted by the nurse in order to make progress in their remission of symptom.